COGNITIVE DEFICITS AND ASSOCIATED NEUROLOGICAL COMPLICATIONS IN CHILDREN WITH DOWN SYNDROME (Western European Journal of Medicine and Medical Science, 2024)
Down syndrome is a hereditary disorder that can result in varying degrees of cognitive impairment and a range of neurological problems. This condition is quite prevalent in neurodevelopment and affects approximately 1 in every 1000 live births globally. This study comprised a group of 120 children, aged 3 to 12 years, diagnosed with Down syndrome. These children were admitted to the clinic “ReaCenter Tashkent” between 2021 and 2023 for treatment of several neurological conditions. The diagnosis was confirmed through the examination of cytogenetic and clinical neurological investigations, which revealed the particular phenotype linked to this syndrome. This article examines specific tests that have been chosen for their capacity to emphasize significant considerations that practitioners should take into account when interpreting IQ test outcomes with this particular group. Statistically, in our research it has demonstrated that the predominant proportion of infants with Down syndrome are born to mothers aged between 26 and 35, accounting for 43 percent of cases. This is a result of the elevated fertility rate within this age group. Concurrently, the fathers’ age at the moment of their child’s birth ranged from 36 to 49 years. Individuals with trisomy had a greater degree of neurological damage in comparison to individuals with mosaic or translocation types. Verbal issues, hand fine motor impairments, deficiencies in the coordination sphere, and autonomic dysregulation were the ways in which these symptoms showed up